Tuning the cell adhesion on biofunctionalized nanoporous organic frameworks - Schmitt, Sophia Katharina; Hümmer, Julia; Kraus, Saskia; Welle, Alexander; Grosjean, Sylvain; Hanke, Maximilian; Rosenhahn, Axel; Bräse, Stefan; Wöll, Christof; Lee‐Thedieck, Cornelia; Tsotsalas, Manuel (Advanced functional materials, 2016)
The ability to control the structure and surface chemistry of biomaterials on a molecular level is crucial for optimizing their performance. Here, a novel type of nanoporous organic framework that is suited for the fabrication of thin films is described. These surface-grafted gels (SURGELs) are prepared and functionalized using two orthogonal, metal-free click chemistries. The SURGELs are shown to be cytocompatible and to efficiently mediate adhesion of osteoblast-like cells. This process can be further enhanced by surface modification. In addition, the use of light-triggered reactions in combination with photomasks allows a patterned functionalization of the substrates. The potential to vary and exactly adjust the parameters within the SURGEL polymer network (including porosity and exact network topology on the nanometer scale as well as addressable functional groups) combined with the ability to functionalize their surfaces with any clickable biomolecule of choice in any desired pattern allow the targeted design of novel SURGEL-based biomaterials for applications in nanomedicine, tissue engineering scaffolds, wound dressing,and medical implants.
Gesehen am 19.05.2020